2002
DOI: 10.1046/j.1369-6513.2002.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Internet interventions for consumers cause more harm than good? A systematic review

Abstract: Objective To systematically review the e ect of consumer use of online health information on decision-making, attitudes, knowledge, satisfaction and health outcomes and utilization. Inclusion criteria All post-1995 comparative studies (including controlled studies, before and after studies, and interrupted time series analyses) of Internet users vs. non-Internet users and other communications mediums, and Internet characteristics such as e-mail vs. other communication mediums, were included. Outcomes included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 27 publications
1
71
0
5
Order By: Relevance
“…[10][11][12][13] A recent review suggested that there was a paucity of evidence showing that consumer use of the internet for health information has any effect on health outcomes. 14 A study investigating which of five media (paper booklet, website, audio, audio plus website, website created using Flash) patients prefer for the delivery of information about cancer suggested that this group preferred the more interactive Flash format, although there was no significant difference in knowledge changes between formats. It should be noted that the study was small (nine participants in each group) and that the focus was on patient preferences rather than knowledge and attitude changes.…”
Section: Refereed Papersmentioning
confidence: 99%
“…[10][11][12][13] A recent review suggested that there was a paucity of evidence showing that consumer use of the internet for health information has any effect on health outcomes. 14 A study investigating which of five media (paper booklet, website, audio, audio plus website, website created using Flash) patients prefer for the delivery of information about cancer suggested that this group preferred the more interactive Flash format, although there was no significant difference in knowledge changes between formats. It should be noted that the study was small (nine participants in each group) and that the focus was on patient preferences rather than knowledge and attitude changes.…”
Section: Refereed Papersmentioning
confidence: 99%
“…The delivery and content of websites is not regulated [22], and it is easy to imagine how variability across websites could make generalizations about this type of intervention problematic. However, it is possible to assess the potential for this kind of intervention to provide smoking cessation support by examining the efficacy of rigorous evaluations carried out to date.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the internet is an important source of information which provides rapid access, it can be overwhelming and difficult for the nonspecialist to know which sites provide current and correct explanations. 8 There are no published papers on the quality and readability of AMD websites. We therefore conducted this study to assess the quality of information and readability of the top internet sites for AMD.…”
Section: Introductionmentioning
confidence: 99%